Fuerza de la ley - Croxatto, Guido Leonardo (2014)
An analysis of Jacques Derrida?s text, The Force of Law, the Mystical\nFoundation of Authority, is submitted. In said text, the author analyses, as indicated\nby the essay title, the foundation (stories and ideas) on which the Law?s authority is\nbased. The purpose is to cross-check the analysis carried out by Derrida of works of\nauthors like Pascal, Montaigne, Walter Benjamin, Kafka, against the current questions\nof legal philosophy, such as the (merely conjectural, hypothetical, presupposed) base\nfor Kelsen?s basic norm (Grundnorm) or the relationship between Law and Morality,\nLaw and Justice, and Law and violence. The key focus on which the author concentrates\nis questioning the concept of violence. He attempts to define who, and why and\nhow, holds ultimate power: the power to proclaim what violent is and is not. ?What\nis the difference between force of law and the mere violence deemed unfair?? This is\nthe key question that inspires Derrida?s text, but it is also the question that has always\ninspired lawyers